Analisis Aplikasi Dana Siap Pakai (DSP) dengan Metode Pieces pada Badan Nasional Penanggulangan Bencana (Indo-MathEdu Intellectuals Journal, 2024)
The submission of requests for Ready Use Fund Assistance (DSP) by the Regional Disaster Management Agency (BPBD) to the National Disaster Management Agency (BNPB) continues to increase along with the number of disaster events. The web-based DSP Application System used by BNPB to manage DSP request documents is no longer in accordance with the current needs of the organization. This study uses the PIECES analysis method which can be considered in developing an information system, in PIECES there are 6 (six) aspects used in analyzing an application or information system, namely Performance, Information, Economic, Control, Efficiency, Service (PIECES), where in each aspect a method and provisions are needed in conducting assessments. The results of the analysis using the PIECES method show that the DSP application has shortcomings in every aspect, the results of the PIECES analysis can be used as a basis for improving the DSP application to meet the needs of users and organizations